Monitoring the commercial potential of intellectual technologies - Kosenko, O. P. (Видавництво Львівської політехніки, 2014)
The model of monitoring the commercial potential level of intellectual technologies (intellectual property objects) using the arctangent function is developed and substantiated. The correlation between the level of the technological product quality and the level of the business risk concerning the product’s introduction and consumption serves as the basis for the model. Four characteristic sets of the monitoring function values are identified; in every set there are provided appropriate recommendations for companies. Розроблено та обґрунтовано модель моніторингу рівня комерційного потенціалу інтелектуальних технологій (об’єктів інтелектуальної власності) з використанням функції арктангенсу. В основу моделі покладено співвідношення рівня якості технологічного продукту та рівня комерційного ризику впровадження і споживання. Виділено чотири характерні множини значень моніторингової функції, в кожній з яких для підприємства наданj відповідні рекомендації.
Моніторинг комерційного потенціалу інтелектуальних технологій
Keywords: monitoring; market attractiveness; intellectual technology; quality; business risk; моніторинг; ринкова привабливість; інтелектуальні технології; якість; комерційний ризик